Causes and management of postharvest losses in Nigeria: an overview - Barau, Bashir; Adelusi, Stephanie Mdazumi; Waiwada, A isha Ahmed; Sani, Musa Gumel (Journal of Postharvest Technology, 2023)
Simple, moderate and advance storage technologies exist and are available in Nigeria with the aim of providing food materials all year  round and preservation of nutritional quality and quantity with additional benefits to the country food security sustainability. The quest for  global food security through healthy food, affordable and sound using available storage technologies and postharvest losses management  could be a major breakthrough nationally using simple to moderate or complex storage technologies based on availability and accessibility  by the value chain actors. Improved production technologies must be couple with good storage technology to curtail postharvest losses  and food insecurity. Affordable technologies that can be handled by farmers from the subsistence level up to large scale production for the  storage of durables crops, perishable crops and semi perishables for farmers/companies exploitation and sustainability have been  developed and are in usage in Nigeria to address food insecurity despite that few storage technologies and recent advances in postharvest  loss management were inadequate. Quantitative and qualitative losses and wastage of food is a major challenge in Sub Sahara Africa  (SSA) which can be tamed through improved usage and popularization of sound storage technologies and good postharvest losses  management. This paper review highlight and review available storage technologies and implication of postharvest losses management in  Nigeria with emphasis on the usage of sound storage technologies to ameliorate postharvest losses in Nigeria..
Keywords: Domestic,; large scale; postharvest losses,; storage,; sub-sahara Africa,; traditional storage